The glucotoxicity protecting effect of honokiol in human hepatocytes via directly activating AMPK - Liu, Hui; Luo, Wu; Liu, Jiazheng; Kang, Xincong; Yan, Jianming; Zhang, Tingting; Yang, Lan; Shen, Lu; Liu, Dongbo (Frontiers in Nutrition, 2022)
Introduction Sustained hyperglycemia causes glucotoxicity, which has been regarded as a contributor to hepatocyte damage in type 2 diabetes (T2D) and its metabolic comorbidities. Honokiol is a natural biphenolic component derived from the dietary supplement Magnolia officinalis extract. This study aimed to investigate the effects of honokiol on glucose metabolism disorders and oxidative stress in hepatocytes and the underlying mechanisms. Methods HepG2 cells were treated with glucosamines (18 mM) to induce glucotoxicity as a diabetic complication model in vitro. Results and discussion Honokiol significantly increased glucose consumption, elevated 2-NBDG uptake, and promoted GLUT2 translocation to the plasma membrane in glucosamine-treated HepG2 cells, indicating that honokiol ameliorates glucose metabolism disorders. Furthermore, glucosamine-induced ROS accumulation and loss of mitochondrial membrane potential were markedly reduced by honokiol, suggesting that honokiol alleviated glucotoxicity-induced oxidative stress. These effects were largely abolished by compound C, an AMPK inhibitor, suggesting an AMPK activation-dependent manner of honokiol function in promoting glucose metabolism and mitigating oxidative stress. Molecular docking results revealed that honokiol could interact with the amino acid residues (His151, Arg152, Lys243, Arg70, Lys170, and His298) in the active site of AMPK. These findings provide new insights into the antidiabetic effect of honokiol, which may be a promising agent for the prevention and treatment of T2D and associated metabolic comorbidities.